PRELIMINARY TECHNOLOGICAL PROPERTIES ASSESSMENT OF BACILLUS SPP. ISOLATED FROM TRADITIONAL CASSAVA STARTERS USED FOR ATTIEKE PRODUCTION - Ayawovi F. Ehon; Regina E. Krabi; Antoine A. Assamoi; Sebastien L. Niamke (European Scientific Journal, ESJ, 2015)
This study was carried out to select Bacillus strains as potential microbial starters for cassava dough fermentation into attiéké (a fermented and steamed granular cassava, couscous-like product) regarding their enzymes (amylase, pectinase, cellulase, phytase, tannase and betaglucosidase) production. For this purpose, 42 presumptive Bacillus spp were isolated from traditional cassava starters and screened in vitro. All the selected strains produced amylase, pectinase, cellulase while 37 (88.09%) produced phytase and 27 (64.28%) were able to produce beta-glucosidase. Regarding these technological properties mainly production of all these enzymes, only 13 Bacillus strains (30.95%) could be used as potential microbial starters in association with lactic acid bacteria for the controlled fermentation of cassava dough in order to improve and standardize the organoleptic quality of attiéké by softening and detoxification actions.